2021
DOI: 10.1186/s12889-020-10110-y
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the hidden: strengthening the HIV surveillance system among key and priority populations in Mozambique

Abstract: High quality, representative data from HIV surveillance systems that have country ownership and commitment are critical for guiding national HIV responses, especially among key and priority populations given their disproportionate role in the transmission of the virus. Between 2011 to 2013, the Mozambique Ministry of Health has conducted five Biobehavioral Surveillance Surveys among key populations (female sex workers, men who has sex with men and people who inject drugs) and priority populations (long distanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…However, the risk profile of FSWs who use illicit drugs in our study is consistent with what has been observed in other studies among key populations (KP) in Mozambique. These studies consistently show that drug use tends to occur more frequently in younger individuals with a higher number of sexual partners, and it is associated with higher HIV and STI prevalence [ 19 , 39 ]. Several additional studies demonstrate that there is a strong relationship between substance use and unsafe sexual practices that increases the risk for HIV and STIs [ 7 , 30 , 36 , 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the risk profile of FSWs who use illicit drugs in our study is consistent with what has been observed in other studies among key populations (KP) in Mozambique. These studies consistently show that drug use tends to occur more frequently in younger individuals with a higher number of sexual partners, and it is associated with higher HIV and STI prevalence [ 19 , 39 ]. Several additional studies demonstrate that there is a strong relationship between substance use and unsafe sexual practices that increases the risk for HIV and STIs [ 7 , 30 , 36 , 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…An estimator is used to produce weights for each participant that are used to generate population proportions of estimates and corresponding standard errors. Details about the survey methodology are described elsewhere [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, an initial respondent is recruited based on network size and they are issued coupons and asked to invite additional participants from within their network. More details about the survey methodology are described elsewhere (10).…”
Section: Survey Design and Participantsmentioning
confidence: 99%
“…High quality, representative data from HIV surveillance systems that have country ownership and commitment are critical for guiding national HIV responses, especially among KPs given their disproportionate role in the transmission of the virus [11]. Key Population specific data are more important than ever to guide the HIV response toward reaching the UNAIDS 95-95-95 targets.…”
Section: Introductionmentioning
confidence: 99%